Can subordinate performance simultaneously reduce leader ostracism and promote leader recognition? A moderated mediation model - Xu, Qin; Huang, Hao; Zhang, Xinran; Zhao, Shuming; Zhou, Lulu (Frontiers in Psychology, 2025)
In recent years, the positive influences of leadership on subordinate performance have been extensively studied. However, whether high-performing subordinates can, in turn, change the way leaders lead them remains underexplored. Based on social exchange theory, this research examines the mediating role of subordinate contribution in the relationship between subordinate performance and leader ostracism and recognition, as well as the moderating role of the leader’s outcome dependence on subordinate. Results from a multi-wave and multi-source field survey comprising 245 subordinates and 68 leaders indicate that subordinate performance increases subordinate contribution, which in turn, reduces leader ostracism and promotes leader recognition. Moreover, outcome dependence on subordinate reinforces the positive impact of subordinate performance on subordinate contribution, and the mediating effect of subordinate contribution. These findings not only provide a theoretical explanation of how and under what conditions subordinate performance can be welcomed by the leader, but also offer valuable insights for organizations to mitigate negative leader responses and foster positive ones.